Cerebral mycotic aneurysms secondary to Streptococcus Agalactiae induced infective endocarditis. (2nd November 2019) - Afshari, Fardad T.; Al-Lawati, Kumayl; Chavda, Swarupsinh; Billing, Stephen; Flint, Graham
Abstract: Subarachnoid and intraparenchymal haemorrhages due to cerebral mycotic aneurysms are rare and associated with high mortality. Streptococcus agalactiae, is a rare cause of endocarditis and there are no reported cases of cerebral mycotic aneurysms secondary to this organism. We report a rare case of streptococcus agalctiae induced intracranial mycotic aneurysm.